Criminal Liability for Cybercrimes in the BRICS Countries - L. Ivanova (BRICS Law Journal, 2023)
One of the areas of cooperation among the BRICS countries is tackling the misuse of information and communication technologies for criminal activities. Each year, the number of cybercrimes continues to grow. Furthermore, the criminal regulation of cybercrimes in each country differs. This article aims to identify the features of criminal liability for cybercrimes in the BRICS countries and offer potential solutions for developing joint legislation initiatives. The primary focus of this discussion is on cybercrime provisions that can be found in the legal acts of the Federative Republic of Brazil, the Russian Federation, the Republic of India, the People’s Republic of China and the Republic of South Africa. The main finding of this research is that the criminal law of each country contains different corpus delicti for dealing with crimes committed in cyberspace. There are also differing conceptions of what constitutes cybercrime. The author proposes the enactment of a common document for the BRICS countries that would contain a shared understanding of cybercrimes as well as the various types of cybercrimes. It is possible to divide cybercrimes into two categories: special cybercrimes committed in the field of computer information and general criminal cybercrimes executed using information technology to commit any other common criminal offences. The results of this research can be used to study the problems of criminal responsibility for cybercrimes in the BRICS countries as well as analyze the ways in which the rules under consideration are actually applied in practice.